Corporate Responsibility and Earnings Management: Does Firm Size Act as a Mediator - Agus Fuadi; Vista Yulianti; Ahmad Bukhori Muslim (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Earnings management remains a major concern in the banking industry because it may reduce the credibility and reliability of financial reporting. At the same time, Corporate Social Responsibility (CSR) has increasingly been recognized as an important governance mechanism that enhances corporate transparency, accountability, and stakeholder trust. However, previous studies have reported inconsistent findings regarding the role of firm size in the relationship between CSR and earnings management. Therefore, this study aims to examine the effect of CSR on earnings management and investigate whether firm size acts as a mediating variable in Indonesian banking companies. This research employed a quantitative explanatory approach using panel data from 22 banking companies listed on the Indonesia Stock Exchange during the 2022–2024 period, resulting in 66 observations. Data were analyzed using panel data regression with the Fixed Effect Model and mediation analysis through the Sobel test using EViews 12. The findings indicate that CSR has a significant negative effect on earnings management and a significant positive effect on firm size. Furthermore, firm size partially mediates the relationship between CSR and earnings management, indicating that CSR reduces earnings management both directly and indirectly through organizational scale. These findings provide theoretical support for stakeholder and legitimacy theories and offer practical insights for managers and regulators in strengthening CSR implementation to improve financial reporting quality and corporate transparency.